THE RELATIONSHIP BETWEEN EATING BEHAVIOR AND NUTRITION INTAKE IN ELDERLY PEOPLE WITH CHOLESTEROL IN SUMBERSECANG VILLAGE, GADING DISTRICT, PROBOLINGGO REGENCY - Liatul Wardah; Ro’isah; H.Nur Hamim (Media Inovasi Pendidikan dan Publikasi, 2023)
Cholesterol is a fatty substance that circulates in the blood, shaped like a wax, which is produced by the liver and is needed by the body. Excessive cholesterol in the blood can form plaques on the walls of blood vessels, causing the lumen to cause atherosclerosis. Elderly with cholesterol, have poor eating behavior that has an impact on low nutritional intake. This study aims to analyze the relationship between eating behavior and nutritional intake in elderly people with cholesterol in Sumbersecang Village, Gading, Probolinggo.This research is a type of correlational analytic research, with a cross sectional research design. This research was conducted in Sumbersecang Village, Gading, Probolinggo in August 2022 which was carried out door to door. The population is 55 respondents. The sampling technique was carried out using Simple Random Sampling. So that the sample is 48 respondents who meet the research inclusion requirements. data collection using editing, coding, scoring and tabulating. The eating behavior research instrument used the Duct Behavior Eating Questionnaire (DBEQ) and nutritional intake using the Nutritional Intake questionnaire. then the data were analyzed using the spearman rank test.The results of this study indicate that most of the eating behavior is not good, namely 29 respondents (60%). And most of the nutritional intake is low, namely 21 respondents (43%). The results of the Spearman rank test found that the value (p = 0.000 < = 0.005.It is believed that the elderly would be able to change their eating habits. Such as not eating only when they see wonderful food. Not eating just because the food looks appetizing, and not eating when they are irritated. In order to ensure that their nutritional needs are also appropriately met.